Rethinking the strategies of Islamic tourism development in Malaysia - Jamil, Nur Diyana Syahirah; Mohd Rezali, Syahindah; Hazizi, Iffah Farzana; Md Sawari, Siti Salwa (Cross-Currents Publishers, 2019)
The tourism industry is one of the contributor on economic growth which has contributed about RM 60.6 billion in tourist arrival from 25.03 million comer in 2012 (Tourism Malaysia, 2013). Luckily, about 55% of the comer were Islamic tourists mostly from Islamic countries. On that case, it can be seen that the demand of Shariah Compliant on tourism industry is expecting increase. The purpose of this study is to point out several rethinking strategies of Islamic tourism development and hospitality which interrelated towards various side of issues in Malaysia. Based on reading various case study and article, the descriptive analysis was used in this study and yet appoint the strategies to enhance the capability of Malaysia in order to ambush the ambition of Islamic tourism development and hospitality. This study also evaluate on several strategies which are the activities (destination), food and beverages and dress code management. From these strategies, the objective of making the Malaysia as Islamic Tourism will accommodate the best services towards Muslim tourist.